75. Image quality and dose measurements in digital breast tomosynthesis. (December 2018) - Ortenzia, O.; Rossi, R.; Bertolini, M.; Nitrosi, A.; Ghetti, C.
Abstract : Purpose: DBT is a three-dimensional reconstruction technique of mammographic images that potentially offers the possibility to overcame the breast tissue-superposition reducing false-positive recalls and increasing cancer detection-rate compared to 2D mammography[1] . The aim of this study is to compare different commercial DBT units in terms of image quality and dose using a set of new phantoms. Methods: The CDMAM phantom was used to compare the Contrast-Details curves in 2D and DBT mode principally for stability assessment. The TomophanTM phantom was used to perform measurements of Slice Sensitive Profile, slice-to-slice incrementation, chest-wall offset, z-axis geometry, Artefact Spread Function, low contrast detectability. An aluminium edge was employed to determine in plane MTF. The Pixmam phantom was used to estimate the AGD and to calculate SDNR. All measurements were performed on reconstructed images. Results: The contrast-details curves are represented in Fig. 1 for all systems. The AGD and SDNR at 45 mm PMMA, the MTF 0.5 in tube-travel and chest wall-nipple directions, the ASF, the SSP and CNRLC are shown inTable 1 . Conclusions: Our results are in good agreement with recent literature reported[2, 3] . It is not simple to compare DBT systems because there are many differences in terms of detection process (direct/indirect), scan angular range, reconstruction algorithms and the presence or not of the grid. The analysis of all collected data can be useful in a contest of a quality assurance program to define a set of values that could be used as benchmarks.